PERANAN BIOLOGI MOLEKULER DAN HTS (HIGH THROUGHPUT SCREENING) DALAM PENGEMBANGAN OBAT SINTETIK BARU - Arief Nurrochmad (Universitas Islam Indonesia, 2004)
ABSTRACTRecently, the discovery of new drugs uses the new concept by modern techniques instead ofthe convenstional techniques. In the development of scientific knowledge, the role of molecularbiology and the modern techniques in the investigations and discovery new drug becomes theimportant things. Many methods and modern techniques use in the discovery of new drugs, i.e,genetic enginering, DNA recombinant, radioligand binding assay technique, HTS techniques (HighThroughput Screening), and mass ligand screening. In this review article, its focus in the role ofmolecular biology and HTS techniques (High Throughput Screening) which accelerated thediscovery of new drugs. The role of molecular biology will be the important things on thecharacteristic of structure of protein target as well as receptor that interact with the drug molecule orligand. By the modelling binding receptor technique, its will be known the conformation of bindingreceptor and ligand in the three dimension. In addition, by the quantum mechanics, molecularmechanics, and molecular dynamics will be identified the active sites, the consuming energy, andthe conformation of the structure of molecule drug as well as the receptor when its interactbiochemicaly. In other hand, the investigation of active compounds from natural resources stillconducted. The investigation of active compound from natural resources, at present use the HTStechniques (High Throughput Screening) could screen thousand extracts combine with HumanGenom Project data in this technique. By the HTS techniques (High Throughput Screening) will beperformed screening extract from the natural resources rapidly. Active compounds resulted fromthis technique, subsequently identified and characterized the structure of molecules and synthesisinstead of natural resources. Finally the compounds could be synthesized in the large scale.Themolecular biology and HTS technique will play the big roles on the discovery of new drugs. Themolecular bology techniques related the protein target and receptor have been changed the newparadigm in the design of new molecule drugs by rationally, wheares the HTS technique willaccelerated sceening active compounds from natural resources.Key words: molecular biology, HTS (High Throughput Screening), new drugs